2021
DOI: 10.3390/nano11010246
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance in the Fabrication of 2D and 3D Metal Carbides-Based Nanomaterials for Energy and Environmental Applications

Abstract: Two-dimensional (2D) nanomaterials have attracted increased interest and exhibited extended applications from nanotechnology to materials science, biomedicine, tissue engineering, as well as energy storage and environmental science. With the development of the synthesis and fabrication of 2D materials, a new family of 2D materials, metal carbides (MCs), revealed promising applications in recent years, and have been utilized for the fabrication of various functional 2D and three-dimensional (3D) nanomaterials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 106 publications
0
29
0
Order By: Relevance
“… 28 , 30 , 36 Typical nanoparticles used so far in drilling mud formulations include but are not limited to carbonaceous nanostructures (carbon, buckminsterfullerene, carbon nanotubes, and graphene), 37 44 copper oxide (CuO), 45 zinc oxide (ZnO), titanium dioxide (TiO 2 ), 46 yttrium oxide (Y 2 O 3 ), ferric oxide (Fe 2 O 3 ), silicon dioxide (SiO 2 ), 47 alumina (Al 2 O 3 ), bismuth ferrite, 48 nanocellulose, nanoclays, and molybdenum disulfide (MoS 2 ). 19 , 21 , 23 , 24 , 26 , 49 53 The fabrication of high-performance hybrid muds based on the association of two or more of the preceding nanoparticles has also been reported. 21 , 23 , 24 , 54 56 …”
Section: Nanoparticles Used As Additives In Drilling Fluidsmentioning
confidence: 99%
“… 28 , 30 , 36 Typical nanoparticles used so far in drilling mud formulations include but are not limited to carbonaceous nanostructures (carbon, buckminsterfullerene, carbon nanotubes, and graphene), 37 44 copper oxide (CuO), 45 zinc oxide (ZnO), titanium dioxide (TiO 2 ), 46 yttrium oxide (Y 2 O 3 ), ferric oxide (Fe 2 O 3 ), silicon dioxide (SiO 2 ), 47 alumina (Al 2 O 3 ), bismuth ferrite, 48 nanocellulose, nanoclays, and molybdenum disulfide (MoS 2 ). 19 , 21 , 23 , 24 , 26 , 49 53 The fabrication of high-performance hybrid muds based on the association of two or more of the preceding nanoparticles has also been reported. 21 , 23 , 24 , 54 56 …”
Section: Nanoparticles Used As Additives In Drilling Fluidsmentioning
confidence: 99%
“…Mxene material is a new 2D layered material, which has the characteristics of high conductivity, hydrophilicity, biocompatibility, large surface area, and easy functionalization, among which good biocompatibility and easy functionalization make it an excellent substrate for the preparation of functional materials for various applications [83]. Through the modification of Mxene materials with amino acids, proteins, and nucleic acids, a functional Mxene colorimetric sensor is designed for the sensitive and efficient detection of specific viruses, bacteria or biomolecules, which has a very wide application prospect.…”
Section: Mxenementioning
confidence: 99%
“…Carbon nanotubes were selected to conduct electricity produced by enzymatic biofuel cells and recorded a voltage of 2.09 V [142]. By adopting the concept of biofuel cells, a bioelectric plaster was fabricated with a current intensity of 1 mA cm −2 that lasted for 12 h [143]. An in vivo study of the bioelectric plaster on the full thickness of the rat wound model showed that ES generated a faster wound closure, and the hydrogel provided a moist microenvironment to reduce wound contracture.…”
Section: Inorganic Conducting Materialsmentioning
confidence: 99%